BILATERAL PNEUMOTHORAX AS A COMPLICATION OF PULMONARY TUBERCULOSIS: A RARE AND LIFE-THREATENING CASE - Amiruddin; Muhammad Rizky Assilmy Lubis (PT. Radja Intercontinental Publishing, 2026)
Introduction: Bilateral spontaneous pneumothorax secondary to pulmonary tuberculosis is an uncommon but life-threatening complication characterized by the rupture of subpleural TB cavities with simultaneous air accumulation in both pleural spaces. It predominantly occurs in patients with advanced cavitary disease or immunocompromise and carries high morbidity and mortality without prompt recognition and management. Early imaging and combined emergency thoracic intervention with anti-tuberculosis therapy are essential to improving patient outcomes. Case Illustrations: A 46-year-old male presented with two months of progressive dyspnea, productive cough, weight loss, night sweats, and acute chest pain. Chest radiography confirmed bilateral pneumothoraces. Bilateral chest tubes were placed, and sputum GeneXpert detected rifampicin-sensitive Mycobacterium tuberculosis. Anti-tuberculosis therapy (Category I regimen) was initiated concurrently. By day 12, air leaks resolved, chest tubes were removed on day 13, and the patient was discharged in stable condition under outpatient TB follow-up. Discussion: Bilateral TB-related pneumothorax arises from cavitary rupture or bronchopleural fistula formation. Although unilateral pneumothorax is well described in TB, bilateral presentation remains rare. Management requires immediate needle decompression or chest tube insertion, high-flow oxygen, nutritional and analgesic support, and prompt initiation of rifampicin-based anti-tuberculosis therapy to address the underlying infection and facilitate cavity healing. Persistent air leaks may necessitate video-assisted thoracoscopic surgery with chemical or mechanical pleurodesis. Close radiological and microbiological monitoring during treatment minimizes recurrence risk. Conclusion: This case underscores the critical need for rapid diagnosis and integrated medical-surgical management of bilateral pneumothorax in pulmonary tuberculosis. Timely chest drainage combined with effective anti-tuberculosis therapy can lead to full lung re-expansion and favorable outcomes, even in resource-limited settings.